PENGARUH KEPUASAN WAJIB PAJAK, INSENTIF PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN TRUST SEBAGAI VARIABEL MODERASI DI KPP PRATAMA LUBUK PAKAM - Raja Guk-Guk, Febri Yanti; Silalahi, Alistraja Dison; Jayusman, Sri Fitria; Harahap, Ardhansyah Putra (Worksheet : Jurnal Akuntansi, 2025)
This research aims to see the role of trust as a moderating factor between dependent and independent variables in KPP Pratama Lubuk Pakam. The method used in research uses quantitative methods. The population in this study is all taxpayers registered with KPP Pratama Lubuk Pakam in 2024 as many as 90,425 people. The sampling technique uses the simple random sampling method with the Slovin formula, so that a sample of 99.98 or 100 taxpayers are obtained registered in KPP Pratama Lubuk Pakam. The analysis method used in this research is multiple linear regression. The data used in this study is primary data. Data analysis techniques include descriptive statistical tests, validity and reliability tests, classical assumption tests, and multiple linear regression tests with the help of SPSS software version 20. The results of the study show that: 1. Taxpayer satisfaction, incentives, and sanctions show an F-calculated value of 16.516 which is greater than F-table 2.47, as well as a significance value of 0.000 which is less than 0.05.2. Satisfaction has a partial and significant effect on taxpayer compliance, which is seen from the t-calculated value (3. 367) which is greater than the t-table (3.367>1.988) with a significance level of 0. 001 which is less than 0. 05. Incentives have a significant influence on taxpayer compliance. It is known that the value of t-calculated (2.107) is greater than the t-table (2.107>1.988) with a significance level of 0. 043 which is greater than 0. 05.4. Sanctions also have a partial and significant effect on taxpayer compliance. The t-calculated value (2.049) is greater than the t-table (2.049 >1.988) with a significance level of 0.038 which is greater than 0.05.